GAMBARAN PERILAKU MENYIKAT GIGI DAN KARIES GIGI PADA SEKAA TERUNA TERUNI WIDYA DHARMA BANJAR TUNJUK TENGAH KABUPATEN TABANAN TAHUN 2019 - Kadek Dean Puspitarini; Ni Wayan Arini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2019)
Good and correct tooth brushing behavior is done diligently and earnestly, carefully means toothbrush is done on the entire surface of the tooth and regularly, done at least twice a day. The purpose of this study is to know the description of the Behavior of Brushing and Dental caries on Sekaa Teruna Teruni Widya Dharma on Village Tunjuk Tengah District Tabanan Regency 2019. This research is a descriptive study using total population of 50 Sekaa Teruna Teruni Widya Dharma. The results of this study showed that people with Sekaa Teruna Teruni who brushed their teeth with the criteria need guidance 72%, enough criteria 18%, good criterion 10%, there is no excellent criteria. Sekaa Teruna Teruni who had dental caries as much as 98%, the average dental caries ie 2.06 included in the low category. It can be concluded that the majority of Sekaa Teruna Teruni behave in tooth brushing with criteria that need guidance. Sekaa Teruna Teruni who suffered from dental caries as much as 98% and the average dental caries of Sekaa Teruna Teruni Widya Dharma was still in the low category.